Mindfulness and Acceptance in Social Work : Evidence-Based Interventions and Emerging Applications. - Boone, Matthew S. (Context Press Mindfulness and Acceptance Practica Series., 2014)
Both social work and psychology stress the importance of understanding and addressing the contextual forces which contribute to human problems. Now, in Mindfulness and Acceptance in Social Work, a clinical social worker brings together the top voices in social work and mindfulness-based treatments in one volume. The book offers social workers an introduction to evidence-based mindfulness concepts and discusses how they can be applied to their profession. It also includes brief interventions that can bring mindfulness and acceptance into daily practice.